Efficacy of a Beauveria bassiana strain, Bacillus thuringiensis and their combination against the tomato leafminer Tuta absoluta - Tsoulnara, Despoina; Port, Gordon (ENTOMOLOGIA HELLENICA, 2016)
A single leaf bioassay was developed to investigate the entomopathogenic efficacy of a Beauveria bassiana strain, Bacillus thuringiensis (Costar®) and their interactions on larval mortality of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae). Tomato leaves were removed from the plants and sprayed with manufacturers’ highest field recommended concentrations for tomato crops before or after infesting the leaves with the larvae. Third instar larvae proved the most susceptible, while susceptibility was lower in the second instar larvae. The combined use showed a higher potential indicating a positive synergistic effect. In addition, treated leaves were sprayed directly with concentrations of 0.0, 0.05, 0.10, 0.15 and 0.20 mL/L of B. bassiana. The efficacy was higher for the tested concentration of 0.20 mL/L that is higher than the recommended dose. The present study suggests that those bioinsecticides have a good potential in the control of T. absoluta.